2009
DOI: 10.1002/smll.200801594
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Deposition of Intact Tetrairon(III) Single‐Molecule Magnets in High‐Vacuum Conditions

Abstract: A tetrairon(III) single-molecule magnet is deposited using a thermal evaporation technique in high vacuum. The chemical integrity is demonstrated by time-of-flight secondary ion mass spectrometry on a film deposited on Al foil, while superconducting quantum interference device magnetometry and alternating current susceptometry of a film deposited on a kapton substrate show magnetic properties identical to the pristine powder. High-frequency electron paramagnetic resonance spectra confirm the characteristic beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 42 publications
(53 reference statements)
0
57
0
2
Order By: Relevance
“…To obtain independent information on magnetic anisotropy, we also recorded W‐band EPR spectra on microcrystalline powder of 2 at 40 K (Figure ). The spectrum shows the typical features observed in several Fe 4 compounds measured at this frequency . Of particular relevance for the determination of the axial zfs parameter D is the low‐field transition, assigned to the M S =−4→ M S =−3 resonance .…”
Section: Resultsmentioning
confidence: 74%
“…To obtain independent information on magnetic anisotropy, we also recorded W‐band EPR spectra on microcrystalline powder of 2 at 40 K (Figure ). The spectrum shows the typical features observed in several Fe 4 compounds measured at this frequency . Of particular relevance for the determination of the axial zfs parameter D is the low‐field transition, assigned to the M S =−4→ M S =−3 resonance .…”
Section: Resultsmentioning
confidence: 74%
“…Successful attempts to deposit SMMs in UHV conditions have been carried out with a tetranuclear iron(III) cluster [ 9 ] and lanthanide bis-phthalocyaninato (LnPc 2 ) complexes. [ 10 , 11 ] For the latter the seminal works of Ishikawa et al [ 12 ] showed that slow dynamics of the magnetization in these mononuclear complexes is originated directly from their strong single ion anisotropy.…”
Section: Doi: 101002/adma201003275mentioning
confidence: 99%
“…1). Within the Fe 4 family, these two clusters are the only ones that have been successfully sublimated in ultra-high vacuum (UHV) conditions, 13,15 preserving unaltered their magnetic properties. The three external Fe III complete their coordination sphere by binding with two b-diketonates (dpm À or pta À ).…”
Section: Introductionmentioning
confidence: 99%